Compared study of routine magnetic resonance imaging and diffusion tensor tractography on the predictive value of diagnosis and prognosis in acute cervical spinal cord injury - Kun Wang; Wen-Tao Wang; Jun Wang; Zhi Chen; Qing-Xin Song; Shi-Yue Chen; Qiang Hao; Da-Wei He; Hong-Xing Shen (Journal of Acute Disease, 2016)
Objective: To compare and analyze the predictive value of two kinds of classification methods, routine magnetic resonance imaging (MRI) and diffusion tensor tractography (DTT), on the diagnosis and prognosis in different degrees of acute cervical spinal cord injury (ACSCI). Methods: A total of 35 patients with ACSCI treated with surgery in our department from January 2013 to December 2014 were included and all patients had received MRI examination and diffusion tensor imaging examination before surgery. The motor score, sensory score and abbreviated injury scale (AIS) of American Spinal Injury Association were used to evaluate the neurological function of patients before and one year after surgery, respectively. Routine MRI was divided into 3 grades according to the compression and signals of spinal cords and DTT was also divided into 3 grades according to continuous levels of fibre bundle. The correlations between routine MRI grades and DTT grades and the neurological function of ACSCI before surgery and after surgery were analyzed, respectively. Results: There were no correlations between MRI grading and the motor score, sensory score and AIS of patients with ACSCI before surgery and after surgery. DTT grading showed no relations with the motor score, sensory score before surgery but were related to AIS before surgery. DTT grading was all related to the motor score, sensory score and AIS after surgery. Conclusions: The noninvasion of DTT showed spinal nerve fibers has a higher predictive value on the diagnosis and prognosis of ACSCI than routine MRI.